The Effect of Debt-to-Equity Ratio, Current Ratio, And Company Size on Price to Book Value - Yuliani, Reva; Dani, Diana Rian (Advantage: Journal of Management and Business, 2025)
This study examines the effect of Debt-to-Equity Ratio (DER), Current Ratio (CR), and Firm Size (SIZE) on Price to Book Value (PBV) of transportation and logistics companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using purposive sampling, this study analyzes 22 companies with a total of 110 firm-year observations. Panel data regression analysis was employed, and based on the Chow, Hausman, and Lagrange Multiplier tests, the Random Effect Model (REM) was selected as the most appropriate estimation model. The empirical results indicate that DER and CR have a positive and significant effect on PBV, suggesting that optimal leverage and adequate liquidity enhance investor confidence and firm value. In contrast, firm size shows a positive but statistically insignificant effect on PBV. Simultaneously, DER, CR, and SIZE significantly influence PBV, confirming the overall suitability of the regression model. These findings imply that effective capital structure and liquidity management play a crucial role in improving firm value in the transportation and logistics sector